Identification of the Scientific Reasoning Ability of Students on Environmental Pollution During the Covid-19 Pandemic - Khoirun Nisa; Hanum Mukti Rahayu; Mahwar Qurbaniah (Journal of Biology Learning, 2023)
This study aims to identify students' scientific reasoning abilities in biology lessons during the Covid-19 pandemic. This research uses descriptive qualitative and quantitative methods. Sampling used a table for determining the number of samples from a certain population with an error rate of 10%, amounting to 131 students. The research samples were 23 students of class VIII A, 23 students of VIII B, 23 students of VIII C, and 23 students of VIII D. The data collection used the scientific reasoning ability test method in the form of an essay. Based on the results of the scientific reasoning ability test, students fall into the less category, namely as much as 55.43%. The research obtained can be concluded that the scientific reasoning ability of students is in the poor category, especially in the indicators of compiling and providing reasons or evidence for the correctness of the solution, drawing conclusions from statements